Prevenzione del mal di schiena di origine meccanica con attività motoria e comportamentale Approfondimenti di patomeccanica e biomeccanica rachidea - MARTINELLI, Elena Anna Rita (Manuali - Biomedica, 2014)
This volume aims at becoming a basic scientific text; by studying the biomechanics of a healthy spine and carrying out a morpho-functional examination of the subject, the possible risks of mechanical damage causing back pain (BP) are analysed, and the preventive and compensatory motor activities for BP are shown in the context of daily life and work activities. The text is up to date on methodological notions and criteria, in particular on the C.A.MO.® method. It offers a broad general cultural platform, and largely fulfils the information requests of fundamental sectors, such as orthopaedics, sports medicine, physiotherapy, kinesiology, sports preparation, work ergonomics.